2017
DOI: 10.1111/mec.13967
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for homosubtypic immunity of influenza H3 in Mallards following vaccination in a natural experimental system

Abstract: The Mallard (Anas platyrhynchos) is an important reservoir species for influenza A viruses (IAV), and in this host, prevalence and virus diversity are high. Studies have demonstrated the presence of homosubtypic immunity, where individuals are unlikely to be reinfected with the same subtype within an autumn season. Further, evidence for heterosubtypic immunity exists, whereby immune responses specific for one subtype offer partial or complete protection against related HA subtypes. We utilized a natural experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…For example, Dugan et al (2008) showed that 26% of 167 wild bird samples carried more than one HA/NA subtype, and that four different genotypes were present in five H4N6 isolates collected from mallards (Anas playrhynchos) at the same location on the same day. Similarly, of 96 virus genomes from mallards isolated in 2011, 56% were reassortants (Wille et al 2013), and using a natural experimental system it was demonstrated that 10 individual sentinel mallards were infected with at least three different subtypes within an autumn season, with 15 HA/NA subtype combinations (Tolf et al 2013;Wille et al 2013Wille et al , 2017. Reassortment in the wild…”
Section: Reassortment In Avian Influenza a Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dugan et al (2008) showed that 26% of 167 wild bird samples carried more than one HA/NA subtype, and that four different genotypes were present in five H4N6 isolates collected from mallards (Anas playrhynchos) at the same location on the same day. Similarly, of 96 virus genomes from mallards isolated in 2011, 56% were reassortants (Wille et al 2013), and using a natural experimental system it was demonstrated that 10 individual sentinel mallards were infected with at least three different subtypes within an autumn season, with 15 HA/NA subtype combinations (Tolf et al 2013;Wille et al 2013Wille et al , 2017. Reassortment in the wild…”
Section: Reassortment In Avian Influenza a Virusmentioning
confidence: 99%
“…Critically, the narrower the transmission bottleneck, the lower the chance of coinfection and reassortment. However, "mixed" influenza virus infections, in which different influenza viruses (A or B), subtypes (H1N1 and H3N2), or lineages/antigenic variants of the same subtype are relatively commonplace within single hosts (Ghedin et al 2009) and frequently observed in avian populations (Dugan et al 2008;Wille et al 2013Wille et al , 2017, provide the raw material for reassortment. Although it is possible that these mixed infections result from relatively "loose" population bottlenecks in some cases, such that multiple viruses are transmitted between hosts (Murcia et al 2010), they may result from the "superinfection" of individual hosts in the face of relatively weak protective immunity.…”
Section: Intrahost Evolution Of Influenza Virusmentioning
confidence: 99%
“…For example, in Monarch butterflies (Danaus plexippus) that have lost migratory behaviour there is an increase in infection risk of a protozoan parasite (Satterfield et al, 2015). The reason for this conflict is unknown, however, one hypothesis is that these studies utilize a chronic disease model, whereas influenza is an acute infectious disease, and dynamics are driven largely by the herd immunity of the population (Latorre-Margalef et al, 2014;van Dijk et al, 2014;Wille et al, 2016a). There are a number of factors which may be important drivers in dynamics of diseases in urban environments, including the relationship between provisioning, stress, pollution and immune response which affect susceptibility and ability to fight infection, however these are challenging to disentangle (Becker et al, 2015;Bradley and Altizer, 2006;Delgado and French, 2012;Patz et al, 2004), and these factors in relation to RNA virus dynamics need to be assessed.…”
Section: Effect Of Urbanization On Rna Virus Dynamicsmentioning
confidence: 99%
“…The study area is an important stopover location for migratory mallards (Anas platyrhynchos, L. 1758), one of the main hosts for lowpathogenic avian influenza viruses (AIV, Webster et al, 1992;Olsen et al, 2006). Through repeated capture and sampling of birds, the scheme has provided a very detailed dataset of viral infections in birds (e.g., see Wallensten et al, 2007;Latorre-Margalef et al, 2009;Gunnarsson et al, 2012) and has been used to investigate the dynamics of different LPAIV subtypes in consecutive years (Latorre-Margalef et al, 2013;Wille et al, 2017), the epidemiological properties of infection (Avril et al, 2016), and the costs of hosts of being infected with LPAIV (Latorre-Margalef et al, 2009;Bengtsson et al, 2016). In addition, the capture-mark-recapture data collected for mallards have been used to estimate population size and emigration probabilities over entire autumn migration seasons (Avril et al, 2016;Wu et al, 2018) to establish patterns of migratory movements (e.g., Gunnarsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%